Magnetically Manipulable Ionic Liquid Crystals Incorporating Neutral Radicals. Issue 3 (3rd February 2022) - Uchida, Yoshiaki; Sakaguchi, Tatsunori; Oki, Shigeaki; Shimono, Satoshi; Park, Jayeong; Sugiyama, Masahito; Sato, Shuichi; Zaytseva, Elena; Mazhukin, Dmitrii G.; Tamura, Rui
Abstract: Invited for this month's cover are the collaborating groups of Dr. Yoshiaki Uchida from Osaka University, Japan, Prof. Rui Tamura and Prof. Masahito Sugiyama from Kyoto University, Japan and Dr. Dmitrii G. Mazhukin from Novosibirsk State University, Russia. The cover picture depicts a contrast between localized spins and conductive ions in the newly‐synthesized ionic liquid crystalline (ILC) nitroxide radicals. The ILC droplet of the new compounds is magnetically manipulable. More information can be found in the Full Paper by Yoshiaki Uchida, Rui Tamura, and co‐workers . Abstract : The synthesis of a new ionic liquid crystal with a nitroxide radical moiety and the magnetic manipulation of a droplet of the compound are described in this work. (DOI: 10.1002/cplu.202100352 ).